1-dodecanol as potential inducer for the FAO1 promoter (PFAO1) in morphologically identified Meyerozyma guilliermondii strain SO - Mahyon, Nur Iznida; Sabri, Suriana; Jijew, George Crisol; Salleh, Abu Bakar; Leow, Thean Chor; Lim, Si Jie; Oslan, Siti Nur Hazwani; Masomian, Malihe; Oslan, Siti Nurbaya (Springer Nature, 2024)
Alcohol oxidase (AOX) oxidizes alcohols to produce carbonyl compounds and peroxides. Its promoter (PAOX1) is widely used in methylotrophic yeasts. A promising yeast expression system (Pichia sp. strain SO) was developed for bacterial lipase expression regulated by PAOX1 of Komagataella phaffii (previously known as Pichia pastoris). However, its unidentified AOX gene and the protein structure have deterred the search for the best inducer. This study was aimed to identify the yeast species and determine the best inducer for PAOX1 upregulation using in silico AOX protein analysis. Morphological (scanning and transmission electron microscopies) and carbon assimilation analyses confirmed isolate SO as Meyerozyma guilliermondii (previously known as Pichia guilliiermondii). Using Hidden-Markov model and degenerate PCR, the LCAO gene (2091 bp) was discovered in M. guilliermondii strain SO. The enzyme, MgFAO1 shared 14% similarity to K. phaffii AOX1 protein (KpAOX1). Molecular docking of MgFAO1 three-dimensional structure predicted using AlphaFold2 showed its preference toward long-chain 1-dodecanol as the substrate unlike KpAOX1 (short-chain methanol). While the alcohol-binding pocket in MgFAO1 was more hydrophobic compared to KpAOX1, 1-dodecanol could be a better inducer for protein expression in M. guilliermondii strain SO. Thus, in silico pipeline employed in this study can help identify homologous proteins in other expression hosts and their preferred substrates for promoter upregulation. However, the computational analyses were merely predictions and further wet-lab validation is required. Yet, this strategy allows cost-efficient screening of potential inducers for microbe-based protein production in the industries, reducing the production cost and offering cheaper options for consumers.